Nexus between Islamic microfinancing and financial wellbeing of micro-entrepreneurs during the Covid-19 pandemic in Malaysia - Nik Hadiyan Nik Azman,; Mohd Zaidi Md Zabri,; Ema Izati Zull Kepili, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Islamic microfinance is expanding and penetrating its potential market over the globe. Access to credit or financing, especially during the COVID-19 pandemic, is vital for micro-entrepreneurs in climbing the socio-economic ladder that will contemporaneously increase their household income. In Malaysia, most of the MEs can hardly access financing from formal financial institutions due to poor credit rating, having zero to little collateral, income instability, small loan amounts, and high transaction costs. Alternatively, MEs approach Islamic microfinance institutions for their financing solution. Therefore, this study intends to investigate how far the utilization of Islamic microfinancing by MEs could enhance their quality of life. One hundred seven (107) usable questionnaires were analysed via the Structural Equation Modelling (SEM) AMOS using IBM® SPSS and found that both investment and expansion factors played key roles in affecting the financial wellbeing of the micro-entrepreneurs. The results lend credence to the positive effect of Islamic microfinance products may have on MEs and indirectly support the long-term economic development for MEs. This study deliver implication to various angles. In practical part, it opens the eyes of micro-entrepreneurs to opt for the right path (expansion and investment) to achieve financial wellbeing. Government (regulators) can enhance the ability of Islamic microfinancing as a tool towards financial wellbeing and in theoretical part, this study deepens the scope of Schumpeter’s theory by inculcate this theory with Islamic finance scope of study.